Reuse of plant-based side streams in food production: Overview of chemical food safety hazards - E.D. van Asselt; N. Dam; W. Tao; N. Meijer; R.M. de Jongh; J.L. Banach (Future Foods)
The European Green Deal and consumer demands drive the increased use of side streams in food production. Although this circular use of materials positively impacts sustainability, it may result in the accumulation or introduction of chemical hazards in the final product. This study explored the potential chemical hazards that can be present in side streams from nine raw materials, i.e., apple, beetroot, carrot, citrus, corn, potato, sugar beet, tomato, and wheat, and brewer’s spent grain (BSG), a side stream from beer production. A structured approach was developed starting from a list of chemical hazards in the raw materials, supplemented with literature information Rapid Alert System for Feed and Food (RASFF) notifications, and expert judgement. All information was combined to provide a list of relevant hazards that could be present in the selected side streams. This study showed that heavy metals, mycotoxins, and plant protection products are most frequently included as relevant hazards. Citrus peel contained the most identified potential chemical hazards (n = 59), whereas root vegetables such as beetroot, sugar beet, and carrot had the lowest number of chemical hazards on the list (respectively 7, 8, and 9). The methodology applied can also be used for side streams from other plant-based raw materials when appropriate data sources are used. The results presented in this study show that this method helps identify potential chemical hazards to be included in monitoring when reusing side streams and can serve as an input for determining chemical food safety in new food product formulations.